2015
DOI: 10.5897/ajest2015.1898
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of biosurfactant produced from submerged fermentation of fruits bagasse of yellow cashew (Anacardium occidentale) using Pseudomonas aeruginosa

Abstract: Biosurfactants are amphiphilic compounds produced by bacteria and fungi to reduce surface and interfacial tension. This work was designed to produce biosurfactants from the fermentation of submerge cashew bagasse (Anacardium occidentale) using a microorganism Pseudomonas aeruginosa. The proximate components of the biosurfactant was determined. Results show that yellow cashew fruit bagasse contains lipid (11.34 ± 0.16%), protein (26.67 ± 0.66%), carbohydrate (49.37 ± 0.60%), moisture (5.78 ± 0.17%), ash (2.70 ±… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…The results from stability tests on the crude biosurfactant which were analyzed by varying some parameters like; pH, temperature, and the salinity (NaCl), to a certain degree and the emulsification index values determined accordingly showed that; the biosurfactants are most stable at pH 8.0 as revealed from the E24 values showing that alkaline medium supported the biosurfactant activity preferentially more than the acidic medium as there was a gradual increase in E24 value from acidic to alkaline region. Though this finding contradict some reviewed works; Anna and Parthasarathi, [31], and Iroha et al [35] who promoted best pH for biosurfactant production to be 7.0 and 6.0 respectively. Optimum pH for this work (pH 8.0) could have resulted from the nature of the carbon source, and/or other environmental conditions prevailing in the course of biosurfactant production.…”
Section: Discussioncontrasting
confidence: 88%
“…The results from stability tests on the crude biosurfactant which were analyzed by varying some parameters like; pH, temperature, and the salinity (NaCl), to a certain degree and the emulsification index values determined accordingly showed that; the biosurfactants are most stable at pH 8.0 as revealed from the E24 values showing that alkaline medium supported the biosurfactant activity preferentially more than the acidic medium as there was a gradual increase in E24 value from acidic to alkaline region. Though this finding contradict some reviewed works; Anna and Parthasarathi, [31], and Iroha et al [35] who promoted best pH for biosurfactant production to be 7.0 and 6.0 respectively. Optimum pH for this work (pH 8.0) could have resulted from the nature of the carbon source, and/or other environmental conditions prevailing in the course of biosurfactant production.…”
Section: Discussioncontrasting
confidence: 88%
“…In addition to wheat straw, yellow cashew fruit bagasse was crushed into powder and mixed with basal mineral medium for rhamnolipids production using P. aeruginosa [ 74 ]. Cashew apple juice was shown to serve as a medium for Acinetobacter calcoaceticus growth and biosurfactant production [ 75 ].…”
Section: Microbial Production Of Rhamnolipids Using Sugar-containing mentioning
confidence: 99%